2020
DOI: 10.1016/j.annonc.2020.03.310
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic and predictive value of the Immunoscore in stage III colon cancer patients treated with oxaliplatin in the prospective IDEA France PRODIGE-GERCOR cohort study

Abstract: Background: The Immunoscore (IS), which prognostically classifies stage IeIII colon cancer (CC) patients, was evaluated in the International Duration Evaluation of Adjuvant Therapy (IDEA) France cohort study investigating 3 versus 6 months of oxaliplatin-based adjuvant chemotherapy in stage III CC patients. Patients and methods: Densities of CD3þ and CD8þ T cells in the tumor and invasive margin were determined by immunohistochemistry, quantified by digital pathology, and converted to IS. Mismatch repair statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 22 publications
10
129
0
1
Order By: Relevance
“…The prognostic value of Immunoscore has been demonstrated in Stage I/II/III, Stage II, Stage III, [6][7][8] and its predictive value of response to chemotherapy demonstrated for randomized phase 3 trial of Stage III patients. 13 These results further reinforce the clinical utility of Immunoscore in Stage IV patients. 1 Tumor and immunological markers are shaping of an efficient immune reaction and can serve as targets for novel therapeutic approaches.…”
Section: Immunoscore For Guiding Patient Management Decisionssupporting
confidence: 53%
“…The prognostic value of Immunoscore has been demonstrated in Stage I/II/III, Stage II, Stage III, [6][7][8] and its predictive value of response to chemotherapy demonstrated for randomized phase 3 trial of Stage III patients. 13 These results further reinforce the clinical utility of Immunoscore in Stage IV patients. 1 Tumor and immunological markers are shaping of an efficient immune reaction and can serve as targets for novel therapeutic approaches.…”
Section: Immunoscore For Guiding Patient Management Decisionssupporting
confidence: 53%
“…The relative contribution of the Immunoscore ® to predict survival was better than the known prognostic factors: N stage, T stage, differentiation, VELIPI, sex, and MSI status [77]. The results of Immunoscore ® in the IDEA-France trial (including 1062 patients), recently published, have confirmed the prognostic value of Immunoscore ® in stage III CC and a beneficial effect of 6 months of FOLFOX/CAPOX in high or intermediate Immunoscore ® patients, independently of high-risk/low-risk group (T4/N2 or T1-3/N1), in contrast to patients with a low Immunoscore, for whom 6 months of treatment did not seem to improve patient outcomes [78]. A recent work using artificial intelligence showed that a predictive nomogram based on immune infiltrates and clinical variables identified a group of patients with less than 10% relapse risk and a group with a 50% relapse risk in stage III patients [79].…”
Section: Biomarkers and Efficacy Of Adjuvant Chemotherapymentioning
confidence: 80%
“…Densities of CD3+ and CD8 + T cells in the tumor and invasive margin of each patient were determined by immunohistochemistry, quantified by digital pathology, and converted into the pre-defined consensus Immunoscore for the 1062 available patients of the study. 3 Immunoscore Low and High were observed in 43.6%, 56.4% of patients, respectively. Immunoscore-Low identified patients at higher risk of relapse or death compared to Immunoscore-High (HR = 1.54; 95% CI, 1.24-1.93, P = .0001).…”
Section: Impact Of Immunity On Colon Cancer Patientsmentioning
confidence: 92%
“…1 The Immunoscore-IDEA France study was conducted in collaboration with PRODIGE, a digestive oncology intergroup gathering the GERCOR, the FFCD and UNICANCER organizations. 2,3 The two studies were performed, using the pre-defined consensus Immunoscore, and included 559 patient samples from the FOLFOX alone arm of the NCCTG-N0147 trial, and 1062 patient samples from both arms (3 vs 6 months) of the IDEA France trial.…”
Section: Impact Of Immunity On Colon Cancer Patientsmentioning
confidence: 99%